2017
DOI: 10.5334/ijic.3474
|View full text |Cite
|
Sign up to set email alerts
|

Identifying strategic opportunities for Māori community organisations to respond to pre-diabetes: Building a platform for integrated care to deliver change that matters to communities

Abstract: Beaton, A et al 2017 Identifying strategic opportunities for Māori community organisations to respond to pre-diabetes: Building a platform for integrated care to deliver change that matters to communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Beaton et al reported the role of Māori Health Organisations, in which kuia, senior older Māori women, play a strong role in spearheading this work. 50 As typical of qualitative studies, this study has sought to explore the views of a limited number of participants in some depth. The focus group interviews were confined to one geographic region and there were no rural participants.…”
Section: People With Prediabetes Viewsmentioning
confidence: 99%
“…Beaton et al reported the role of Māori Health Organisations, in which kuia, senior older Māori women, play a strong role in spearheading this work. 50 As typical of qualitative studies, this study has sought to explore the views of a limited number of participants in some depth. The focus group interviews were confined to one geographic region and there were no rural participants.…”
Section: People With Prediabetes Viewsmentioning
confidence: 99%